The shear bond strength of reconditioned sapphire bracket after rebonding with sandblasting zirconia - Pitriani, Dedeh; Logamarta, Setiadi W; Imam, Dian N. Agus (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2018)
Introduction: Sapphire bracket is the best aesthetic bracket with metal bracket-like mechanical properties. In conditions causing attachment lost between sapphire bracket and enamel, a rebonding procedure will needed. The shear bond strength of sapphire bracket decrease after the rebonding procedure. Sandblasting, hydrofluoric acid etching, and silanization as surface treatment are widely used to improve the bracket bond strength. The purpose of this study was to evaluate the effect of zirconia as sandblasting material towards the shear bond strength of reconditioned sapphire bracket. Methods: This study was an experimental laboratory with as much as 27 samples of sapphire bracket divided into 3 groups. Group I was rebonded with sandblasting zirconia and silane, group II with hydrofluoric acid etching and silane, and group III with new bracket bonding. The attachment strength measurement indicator was the shear bond strength test and the SEM analysis. Results: The shear bond strength test showed the average value for each group were 12.97 MPa, 9.26 MPa, and 10.58 MPa, consecutively. The test results were then analysed using a one way ANOVA and LSD (p < 0.05), which showed that significant difference only found in the comparison between group I with group II, but not in the comparison between group I with group III. The SEM analysis result showed that sandblasted surface has homogenous microporosities in high quantities. Conclusion: Zirconia as sandblasting material was effective in increasing the shear bond strength of reconditioned sapphire bracket.